The use of scaning electron microscopy in postvaccinal evaluation of tracheal epithelium of Coturnix coturnix japonica - Santin,Elizabeth (2003)
This study aimed at evaluating the use of scanning electron microscopy in the study of the post-vaccinal respiratory reaction of the tracheal epithelium of quails (Coturnix coturnix japonica) immunized against Newcastle disease. A number of 36 quails were distributed into four groups: T1 ¾ control birds (non-vaccinated); T2 ¾ birds vaccinated with Ulster 2C strain; t3 ¾ birds vaccinated with B1 strain; t4 ¾ birds vaccinated with LaSota strain. Regardless the experimental group, birds did not show detectable clinical signs of post-vaccinal respiratory reaction. However, the analysis of tracheal fragments by scanning electron microscopy showed that birds vaccinated with B1 and LaSota strains developed epithelial sloughing of the trachea, whereas those vaccinated Ulster 2C strain did not develop this change, demonstrating intact tracheal epithelium, similar to the control group.